2018
DOI: 10.1038/s41380-018-0274-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic intersection of BDNF Val66Met genotype with premenstrual dysphoric disorder transcriptome in a cross-species model of estradiol add-back

Abstract: Premenstrual dysphoric disorder (PMDD) affects over 5% of women, with symptoms similar to anxiety and major depression, and is associated with differential sensitivity to circulating ovarian hormones. Little is known about the genetic and epigenetic factors that increase the risk to develop PMDD. We report that 17β-estradiol (E2) affects the behavior and the epigenome in a mouse model carrying a single-nucleotide polymorphism of the brain-derived neurotrophic factor gene (BDNF Val66Met), in a way that recapitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Recent studies have pointed to molecular mechanisms, in terms of gene expression and epigenetic modifications, of such sensitivity to ovarian hormone changes, in particular estrogen sensitivity (Guintivano, Arad, Gould, Payne, & Kaminsky, 2014; Mehta et al., 2014). Finally, the ovarian hormone sensitivity hypothesis is indirectly strengthened by observations in women with premenstrual dysphoric disorder (PMDD) who indeed develop depressive symptoms when exposed to ovarian steroid hormone replacement after a period of hormonal suppression (Schmidt et al., 2017), which again seem to involve epigenetic mechanisms related to estradiol (Marrocco et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have pointed to molecular mechanisms, in terms of gene expression and epigenetic modifications, of such sensitivity to ovarian hormone changes, in particular estrogen sensitivity (Guintivano, Arad, Gould, Payne, & Kaminsky, 2014; Mehta et al., 2014). Finally, the ovarian hormone sensitivity hypothesis is indirectly strengthened by observations in women with premenstrual dysphoric disorder (PMDD) who indeed develop depressive symptoms when exposed to ovarian steroid hormone replacement after a period of hormonal suppression (Schmidt et al., 2017), which again seem to involve epigenetic mechanisms related to estradiol (Marrocco et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers then established that the greater reactivity was due to specific genetic variations that led to overexpression of some cellular responses and underexpression of others 129 . These findings were replicated in animal models of PMDD 130 . This research revealed an underlying dysfunction of genetic response to hormone fluctuation that supports the idea that PMDD is a categorical disorder.…”
Section: The Focus Of Psychiatric Physicians Should Be Particularly On the Biological Aspects Of Mental Illnessmentioning
confidence: 83%
“…In a mouse model, a single-nucleotide polymorphism in the brain-derived neurotrophic factor (BDNF) gene induces anxiety-like and depression-like behavior in response to estradiol administration, similarly to what occurs in women with PMDD 83 .…”
Section: Geneticsmentioning
confidence: 99%
“…Finally, recent findings focused on genetic variations involving the GABAergic system, establishing for the first time an association between PMDD and copy number variations in the GABRB2 gene encoding for a GABA-A receptor subunit 84 . Thus, genetic and epigenetic studies may shed light on a possible behavioral sensitivity to ovarian sex steroids and may pave the way to novel targets for therapy 83 .…”
Section: Geneticsmentioning
confidence: 99%